State of duodenal mucosa in rats after epichlorohydrin long-acting - M. A. Mirzebasov; A. S. Smirnov; S. N. Smirnov (Kazimierz Wielki University, 2018)
Introduction. A significant problem of modern humankind is the problem of environmental pollution. One of the anthropogenic pollutants is epichlorohydrin (ECH). However, the character of the effect of ECH on the duodenum was not studied. The aims of the study are the investigation the changes in duodenum due to the long-term effects of ECH іn rats. Material and methods of the research. Experimental rats of 1-st group were rats for control. The rats of the 2-nd group received ECH. Rats of group 3 received Echinacea purpurea EP extract. Rats of the 4-th experimental group received thiotriazoline. Rats of the 5-th group received ECH and EP extract. Rats of the 6-th group received ECH and thiotriazoline. Results of the research and their discussion. Under action of epichlorohydrin the thickness of the duodenal mucosa decreases. EP extract, as well as thiotriazoline, cause an increase in the thickness of the duodenal mucosa of rats not receiving epichlorohydrin. In case of thiotriazoline use, the increase in the thickness of the duodenal mucosa was more expressiveness and longer. It was established that the administration of the EP extract, as well as the use of thiotriazoline on the background of action of epichlorohydrin leads to a decrease in the expressiveness and duration of decrease the duodenal mucosa thickness induced by the influence of epichlorohydrin. Conclusions. The results indicate the possibility of using these drugs in order to correct of the epichlorohydrin's effects.